Defect Engineering in Metal‒Organic Frameworks as Futuristic Options for Purification of Pollutants in an Aqueous Environment - Cao, Yuhua; Mi, Xin; Li, Xiang; Wang, Bo (Frontiers in Chemistry, 2021)
Clean water scarcity becomes a more important issue in the world wide. The water treatment industry demand novel effective materials in the future. Defect engineering for nanoparticles is among the most revolutionary technologies around the world. Because of high surface area, structural diversity and tailor ability, Metal Organic Frameworks (MOFs) is found from a variety of applications including separation, storage, sensing, drug delivery and many other issues. The application in wastewater treatment associated with water stable MOF-based materials is an emerging research topic in recent decades. Defect engineering is a sophisticated technique to manufacture defects and change the geometric frameworks and chemical environment of a target compounds. Since MOFs have a series of designable structure and active sites, tailoring materials properties in MOFs by defect engineering is a novel concept. Defect engineering will be excavating hidden active sites in MOFs, which can lead to better performance in many application fields. Therefore, this technology will open new opportunities in water purification process. There have so far been few efforts to comprehensively discuss this research area. In the review, we provide an overview in the development of defect-engineered materials in Metal Organic Frameworks (MOFs) for water purification process, furthermore, we discuss the potential applications of defect-engineered materials in the future.